Is short term debt maturity linked to real earning management - Nguyen Thanh Liem; Trinh Quoc Trung; Nguyen Vinh Khuong; Cao Thi Mien Thuy (Zielona Góra: Faculty of Economics and Management Press)
This paper explores the association between the maturity of short term debt and real earnings management in the context of an emerging market. We use a panel dataset of listed firms in Vietnam over the period from 2009 to 2017 and employ conventional methods for panel data analysis.
Keywords: real earnings management; debt maturity; short-term load; information asymmetry; zarządzanie realnymi zarobkami; zapadalność długu; kredyt krótkoterminowy